2020
DOI: 10.3390/polym13010017
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Biodegradation by Tenebrio molitor Larvae: Identification of Generated Substances Using a GC-MS Untargeted Screening Method

Abstract: A GC-MS method has been applied to screen and evaluate the generation of chemical compounds during the biodegradation of polystyrene (PS) with Tenebrio molitor larvae. Several resulting compounds have been identified, including trimers 2,4,6-triphenyl-1-hexene and 1,3,5-triphenylcyclohexane, the volatiles acetophenone and cumyl alcohol, and 2,4-di-tert butylphenol, a non-intentionally added substance (NIAS) present in the plastic material. The PS monomers styrene and α-methyl styrene were also identified in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…This trend can be explained by the enzymatic conversion of ingested compounds into CO 2 , as already reported by Yang et al (2015c). In parallel, Tsochatzis et al (2021) identified several bioactive components, such as myristic, palmitic and oleic acids and their respective amides. The authors concluded that the absence of hazardous chemicals in TM biomass and the presence of bioactive molecules suggest that plastic biodegradation by TM appears to be a valid bio-recycling process.…”
Section: Biodegradation Of Plastic Wastesupporting
confidence: 75%
See 2 more Smart Citations
“…This trend can be explained by the enzymatic conversion of ingested compounds into CO 2 , as already reported by Yang et al (2015c). In parallel, Tsochatzis et al (2021) identified several bioactive components, such as myristic, palmitic and oleic acids and their respective amides. The authors concluded that the absence of hazardous chemicals in TM biomass and the presence of bioactive molecules suggest that plastic biodegradation by TM appears to be a valid bio-recycling process.…”
Section: Biodegradation Of Plastic Wastesupporting
confidence: 75%
“…In a 7-day test, they identified several oligomers resulting from PS biodegradation, such as PS monomers (e.g. styrene, α-methyl styrene, acetophenone), oligomers and other unintentionally added substances (Tsochatzis et al 2021). For all residual substances (except α-methyl styrene which reaches a plateau up to day 7), after an initial increase from day 1 to day 3, a decrease is observed on day 7.…”
Section: Biodegradation Of Plastic Wastementioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing interest in the biodegradation of plastics, by microbial activity or specific enzymatic activity. In particular, studies have reported the potential degradation of PS using different insects: mealworms (Tenebrio molitor) [4][5][6][7][8][9][10], superworms…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics studies have revealed the presence of several bioactive compounds, in both the bulk insects' biomass and frass, such as long-chain fatty acids, esters and amides. Furthermore, it has been shown that alteration in feeding affects the ratio of these compounds, with several long-chain acids, in addition to hydrocarbons, present in connection with the presence of PS and its degradation [4,6,7]. The addition of PS to the diet causes the insects to experience metabolic stress, in comparison to a control diet [4,6,7].…”
Section: Introductionmentioning
confidence: 99%